Women in Southeast Asian Nationalist Movements - Blackburn, Susan; Ting, Helen (NUS Press, 2013)
Books on Southeast Asian nationalist movements make very little - if any - mention of women in their ranks. Biographical studies of politically active women in Southeast Asia are also rare. This book makes a strong case for the significance of women's involvement in nationalist movements.The authors show women negotiating their own subjectivity and agency at the confluence of colonialism, patriarchal traditions, and modern ideals of national and personal emancipation. They also illustrate the constraints imposed on them by wider social and political structures, and show what it was like to live as a political activist in different times and places Fully documented and drawing on wider scholarship, this book will be of interest to students of Southeast Asian history and politics as well as readers with a particular interest in women, nationalism and political activism.